NYPD Blue. Season 01 - Caruso, David, 1956-; Franz, Dennis; Stringfield, Sherry, 1967-; Brenneman, Amy.; Turturro, Nicholas; Milch, David, 1945-; Bochco, Steven; Post, Mike.; McDaniel, James, 1958-; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2002)
Drama set at the 15th Precinct in New York City portrays the work and personal lives of police officers.
Disc 1. Episodes 1-4. Pilot ; 4B or not 4B ; Brown appetit ; True confessions -- disc 2. Episodes 5-8. Emission accomplished ; Personal foul ; NYPD Lou ; Tempest in a c-cup -- disc 3. Episodes 9-12. Ice follies ; Oscar, Meyer, wiener ; From hare to eternity ; Up on the roof -- disc 4. Episodes 13-16. Abandando abandoned ; Jumpin' Jack Fleishman ; Steroid Roy ; A sudden fish -- disc 5. Episodes 17-20. Black men can jump ; Zeppo marks brothers ; Serge the concierge ; Good time Charlie -- disc 6. Episodes 21-22, and bonus features. Guns 'n' roses ; Rockin' Robin.
Title from disc surface.
Originally produced as 20 episodes of the 1993-1994 season of the television series.
Special features: one-hour "Making of Season One" documentary ; all new "Love on NYPD Blue" and "Cast Blotter" featurettes ; selected episode commentaries ; script-to-screen comparison.
Executive producers, David Milch & Steven Bochco ; music, Mike Post.
David Caruso, Dennis Franz, James McDaniel, Sherry Stringfield, Amy Brenneman, Nicholas Turturro.
MPAA rating: Not rated.
Keywords: New York (N.Y.). -- Police Department. -- Drama; Detectives -- New York (State) -- New York -- Drama; Criminal investigation -- New York (State) -- New York -- Drama; Films for the hearing impaired; Television programs -- United States; Television serials